A five‐step risk management process for geriatric dental practice during SARS‐CoV‐2 pandemic. (25th September 2020) - Sivaraman, Karthik; Chopra, Aditi; Narayana, Aparna; Radhakrishnan, Raghu A.
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) is an RNA virus that causes coronavirus infection (COVID‐19). COVID‐19 is a highly contagious disease transmitted through respiratory droplets, saliva and other contact routes. Within 10 months of its outbreak, SARS‐CoV‐2 has infected more than 23 million people around the world. Evidence suggests that older adults are the most vulnerable to infection and have an increased risk of mortality. Reduced immunity and underlying medical conditions make them risk‐prone and vulnerable to critical care. Older adults affected with the SARS‐CoV‐2 virus present with distinct clinical manifestations necessitating specific treatment needs and management protocols. While it is crucial to prevent the spread of novel coronavirus (2019‐nCoV), the role of oral healthcare workers in addressing the specific needs of ageing adult patients by adopting specific guidelines and appropriate infection control protocols is timely. This paper aims to develop specific guidelines and protocols for the dental management of geriatric patients during the COVID‐19 pandemic.